Pengaruh Pengetahuan Kewirausahaan, Lingkungan Keluarga, Dan Kreativitas Terhadap Minat Berwirausaha - Dewi Apriani Fristianingroem; Resti Widasari (Antroposen: Journal of Social Studies and Humaniora, 2024)
This research aims to determine the presence or absence of the influence of entrepreneurship knowledge, family environment, and creativity on the entrepreneurial interest of 11th-grade students in BDP (Business and Management) class at State Vocational High School 1 Slawi. This type of research is an ex-post facto study with a quantitative approach and literature review. A total of 92 samples were taken using simple random sampling from a population of 140 students. Data collection methods used were observation, documentation, and questionnaires. The data analysis techniques employed included descriptive analysis, simple regression analysis, multiple regression analysis, and hypothesis testing conducted through partial significance testing and simultaneous significance testing processed using SPSS version 21. The results of this research indicate (1) a positive and significant influence of entrepreneurship knowledge on entrepreneurial interest by 18.3%, (2) a positive and significant influence of the family environment on entrepreneurial interest by 30.7%, (3) a positive and significant influence of creativity on student entrepreneurial interest, and (4) a positive and significant influence of entrepreneurship knowledge and family environment on entrepreneurial interest by 36.9%. Based on the research findings, it is expected that entrepreneurship learning, both theoretical and practical, be conducted more optimally, students become more active in learning and implementing entrepreneurship knowledge to start their entrepreneurial ventures, and families provide support, both financial and non-financial, for their entrepreneurial endeavors.